PENDIDIKAN AKHLAK KEPADA ANAK DENGAN METODE HABITUASI (Kajian Hadits Dalam Perspektif Psikologi) - Idail Uzmi Fitri Umami (Universitas Islam Negeri Mataram, 2018)
Moral education for children is very important because children are the next generation of religion, nation and state, imagine how a country would become if its successor or leader does not have morals and morals, of course, what happens is chaos in that country. Moral education for someone should be early because morality is the embodiment of personality that is nurtured from the beginning, fostering good moral character for children certainly starts from the smallest environment of his life, namely the family environment. But the problem that arises is how to educate children correctly and effectively, a term known in children’s temperament is the tabula rasa expression which means the child is born like blank paper and innocently does not have any scribble at all that the child carries nothing when born, so this It is the duty of parents to direct their children to the right path or to the wrong road.